PENINGKATAN PEMAHAMAN MASYARAKAT TERHADAP PAJAK UMKM KECAMATAN BAYANG KABUPATEN PESISIR SELATAN DALAM MENHADAPI PERSAINGAN BISNIS - Syaiful, Syaiful; Yulihardi, Yulihardi; Afrida, Afrida; Amrullah, Amrullah (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
: Fostering tax awareness among the community is very important so that the community as taxpayers, both as corporate taxpayers and individual taxpayers for the next period will become taxpayers who are always aware of taxes. Understanding by the community, whether it is an individual or an entrepreneur owning a Business Entity will benefit the community and the country, because we fully realize that taxes are very important for the sustainability of the development of the Nation and State. Ge Sapa or Generation of Tax Understanding was formed as an alternative solution that aims to assist the Director General of Taxes in increasing tax awareness. Ge Sapa comes from the Javanese word dingge sopo which means for whom. Ge Sapa was formed with the hope of providing tax awareness that will later affect the level of Indonesian tax compliance. Through Ge Sapa, it will indirectly make taxpayers understand that the tax collection will return to the interests of the people themselves.